Second language learning theories - Mitchell, Rosamond (New York ; London : Routledge ; Taylor & Francis Group, 2019)
Written by a team of leading experts working in different SLA specialisms, this fourth edition is a clear and concise introduction to the main theories of second language acquisition (SLA) from multiple perspectives, comprehensively updated to reflect the very latest developments SLA research in recent years. The book covers all the main theoretical perspectives currently active in SLA and sets each chapter within a broader framework. Each chapter examines the claims and scope of each theory and how each views language, the learner and the acquisition process, supplemented by summaries of key studies and data examples from a variety of languages. Chapters end with an evaluative summary of the theories discussed. Key features to this fourth edition include updated accounts of developments in cognitive approaches to second language (L2) learning, the implications of advances in generative linguistics and the "social turn" in L2 research, with re-worked chapters on functional, sociocultural and sociolinguistic perspectives, and an entirely new chapter on theory integration, in addition to updated examples using new studies. Second Language Learning Theories continues to be an essential resource for graduate students in second language acquisition.